2017
DOI: 10.1515/acph-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

The role of peroxisome proliferator-activated receptor in the treatment of non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) has been defined as a spectrum of histological abnormalities and is characterized by significant and excessive accumulation of triglycerides in the hepatocytes in patients without alcohol consumption or other diseases. Current studies are targeting new molecular mechanisms that underlie NAFLD and associated metabolic disorders. Many therapeutic targets have been found and used in clinical studies. Peroxisome proliferator-activated receptors (PPARs) are among the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Which contribute to the complex regulation of NAFLD progression, and was the therapeutic target of anti-NAFLD compounds. Recent research found that PPARs were closely related to metabolic syndrome and its relevant complications [29]. PPARs pathway had protective effect on the NAFLD development because it could regulate the lipid metabolism [30].…”
Section: Discussionmentioning
confidence: 99%
“…Which contribute to the complex regulation of NAFLD progression, and was the therapeutic target of anti-NAFLD compounds. Recent research found that PPARs were closely related to metabolic syndrome and its relevant complications [29]. PPARs pathway had protective effect on the NAFLD development because it could regulate the lipid metabolism [30].…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation at the PPAR‐α gene may distinguish between NAFLD patients with mild and severe fibrosis . PPAR‐α agonists could improve serum ALT levels in NASH patients . In addition to PPAR‐α, other genes in the PPAR subfamily were also involved in NAFLD management.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three isotypes, PPAR‐α and PPAR‐γ have been frequently reported in the pathogenesis of NAFLD. The balance of PPAR activity is associated with various mechanisms, including the induction of gene expressions involved in decreasing oxidative stress (OS) and increasing the secretion of beneficial adipokines and anti‐inflammatory factors . Studies in animals and humans have revealed that PPAR agonists, such as glitazones, protect against NAFLD and have been clinically used to treat NAFLD and MS. Glitazones may ameliorate steatosis and inflammation of NASH, although they have no impact on improving fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is one of the key mechanisms responsible for disease progression in NAFLD [ 3 ]. Recent studies have shown that fatty acids could induce oxidative stress through regulating the expression or activity of key nuclear receptors such as PPAR α , β , γ , liver X receptor (LXR α ), retinoid X receptor (RXR α ), SREBP-1c, and others [ 4 , 5 ]. Oxidative stress may produce peroxides and free radicals that further induce haptic cell damage and cell death in NAFLD patients [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%